Current prescription status of antihypertensive drugs in Japanese patients with hypertension: Analysis by type of comorbidities. (3rd April 2019) - Ishida, Takayuki; Oh, Akinori; Hiroi, Shinzo; Shimasaki, Yukio; Tsuchihashi, Takuya
ABSTRACT: In 2014, the Japanese Society of Hypertension (JSH) issued revised guidelines for hypertension management. To assess adherence to the guidelines, this retrospective study evaluated the real-world status of antihypertensive drug prescribing for Japanese patients with hypertension, classified by comorbidity: diabetes mellitus, dyslipidemia, gout/hyperuricemia and renal diseases. Data on 59, 867 hypertensive patients who received their first prescription for antihypertensive therapy between April 2014 and March 2015, were obtained from a medical insurance claims database for hospitals participating in the Diagnosis Procedure Combination/Per-Diem payment system. The most common drugs prescribed for each comorbidity subgroup were calcium channel blockers (CCBs) and angiotensin II receptor blockers (ARBs), with prescription rates of around 60–70%. Contrary to JSH recommendations, diuretics and angiotensin-converting enzyme inhibitors were prescribed less often than β-blockers. Whereas diabetes mellitus is a compelling indication for use of renin-angiotensin system inhibitors, CCBs were commonly prescribed in this subgroup. The treatment pattern for patients with comorbid dyslipidemia closely resembled that for the overall patient population. Loop diuretics were prescribed more frequently for patients with renal diseases or gout/hyperuricemia than for those with diabetes mellitus or dyslipidemia. Although antihypertensive drug prescribing varied by comorbidity, JSH 2014 guidelines appeared not to be incorporated adequately into actual clinical practice.